(3JMaI GdehGdi HTQM Sdc YbO GddBdi aj GdeNeS GdNGdis - (3eMeO Hf bGSe Hf GdbGVis; (3eMeO Hf Gdhdj GdUGdM cQe Gddg GdUhajs
(3ChdgG (B:s
(3hHYO ajbhd eMeO Hf bGSe Hf GdbGVi deG hbYJ Ydi fXe UajfG Gdabjg GdYdGeI eMeO Hf Gdhdi GdUGdM ai cjajI JUQja GdeNeS GdNGdj GdhSW hSejJg JMag GdehGdi ai TQM YbO GddBdi ai GdeNeS GdNGdj s
(3BNQgG (B:s
(3hefge HYVge abSe GdedGFcI GdCQHY bSejf hHYVge CQHYI CbSGe ceG JbOe hbO Je eWdhHfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdeLGejYs